Exploring the Brand Effect of Islamic Bank on the General Population of Scotland - Jacob Jackson; Fawad Khaleel (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
The United Kingdom (UK) currently has one of the most attractive regulatory and tax systems in the world for Islamic finance, as well as being far ahead of other western nations for provision of Islamic finance, with five sharia-compliant banks. Yet despite this, the patronage of these banks is extremely low, often times below that of smaller building societies. While the largest Islamic bank in the UK, Al Rayan (formerly Islamic Bank of Britain), have one third of its customer base have religious affiliations other than Islam, and a further 80% of all fixed-term deposits also patroned by non-Muslims. This study explores why general consumers do not pursue patronage with Islamic banking.This is an inductive research enquiry that uses descriptive statistics within a social constructivist paradigm to construct a line of reasoning, based on the primary data is collected through detailed questionnaire (n=29).The findings from this research highlight the need for Islamic banks to better fund information programmes, advertisements and promotions to further spread awareness of their offerings as consumers are positive in their reception to Islamic finance concepts but unaware of its offerings.